Patterns of end-of-life hospital care for patients with non-Hodgkin lymphoma: exploring the landscape. Issue 8 (3rd July 2019) - Philip, Jennifer; Collins, Anna; Ritchie, David; Le, Brian; Millar, Jeremy; McLachlan, Sue-Anne; Krishnasamy, Meinir; Hudson, Peter; Sundararajan, Vijaya
Abstract: Rapid change, treatment responsiveness, and prognostication difficulties present challenges for palliative care integration for hematology patients. This Australian study aimed to document end-of-life hospital care for patients with non-Hodgkin lymphoma (NHL) to consider opportunities for palliative care integration. A retrospective population cohort design examining existing linked datasets of health service utilization and death registration. The results revealed 4380 NHL patients, majority male (58%) and aged 70+ years (70%), spent 32 days (median) in hospital in final 6 months of life, and in the last month, 56% had more than 1 hospital admission, and 57% stayed more than 14 days. Forty-one percent accessed palliative care, with first contact 23 days (median) before death, and for 77% in final admission. Early palliative care was more likely for patients with greater symptom burden. This study mapping patterns of care for patients who die from NHL establishes a baseline enabling comparisons for future care innovations.